Investigating the reactivity of neutral water-soluble Ru(ii)–PTA carbonyls towards the model imine ligands pyridine and 2, 2′-bipyridine. Issue 45 (16th July 2020) - Battistin, Federica; Vidal, Alessio; Balducci, Gabriele; Alessio, Enzo
Abstract : The reactivity of selected Ru(ii )-PTA carbonyls with potentially labile ligands ( i.e. H2 O, dmso and/or Cl) towards the model imine ligands pyridine and 2, 2′-bipyridine was investigated, yielding several neutral and cationic water-soluble derivatives. Abstract : As a continuation of our strategy for preparing new Ru(ii ) precursors to be exploited as building blocks in the construction of metal-mediated supramolecular assemblies with improved solubility in water, here we describe the reactivity of selected neutral Ru(ii )–PTA carbonyls (PTA = 1, 3, 5-triaza-7-phosphaadamantane) towards the model imine ligands pyridine (py) and 2, 2′-bipyridine (bpy) and the preparation and characterization of several neutral and cationic water-soluble derivatives: trans, trans, trans -[RuCl2 (CO)(py)(PTA)2 ] (7 ), cis, cis, trans -[RuCl2 (CO)2 (py)(PTA)] (9 ), cis, trans -[Ru(bpy)Cl(CO)(PTA)2 ]Cl (10 ), mer -[Ru(bpy)(CO)(PTA)3 ](Cl)2 (12 ), cis, trans -[Ru(bpy)(CO)2 Cl(PTA)]Cl (13 ), cis, trans -[Ru(bpy)(CO)2 (PTA)2 ](NO3 )2 (14NO3 ). In addition, we found that light-induced isomerization in some bpy compounds could be induced. The following species, either side-products isolated in low yield or compounds obtained exclusively in solution, were also unambiguously identified: cis, cis, trans -[RuCl2 (CO)(py)(PTA)2 ] (8 ), trans -[RuCl2 (bpy)(CO)(PTA)] (11 ), cis, cis -[Ru(bpy)Cl(CO)(PTA)2 ]Cl (15 ) and cis, cis -[Ru(bpy)(CO)2 Cl(PTA)]Cl (16 ). The X-ray structures of 7, 11 ·H2 O, and 12 ·7H2 O are also reported. All compounds are new and – with few exceptions – show a good solubility in water.